Plasmodium Falciparum Malaria: AN AMELANOTIC MELANOMA CELL LINE BEARS RECEPTORS FOR THE KNOB LIGAND ON INFECTED ERYTHROCYTES - Schmidt, John A. (1982)
Erythrocytes infected with Plasmodium falciparum trophozoites and schizonts are not seen in the peripheral circulation because they attach to venular endothelium via knoblike structures on the infected erythrocyte membrane. We have recently shown that erythrocytes containing P. falciparum trophozoites and schizonts likewise attach to cultured human venous endothelial cells via knobs. In search of a more practical target cell for large scale binding studies designed to characterize and isolate the knob ligand, we tested various normal cells and continuous cell lines for their ability to bind P. falciparum-infected erythrocytes. Of the 18 cell types tested, binding of infected erythrocytes was observed to a human amelanotic melanoma cell line and amnion epithelial cells as well as to human aortic and umbilical vein endothelial cells. 96-100% of amelanotic melanoma cells bound 17±4 (±1 SEM) infected erythrocytes per positive cell, whereas fewer endothelial cells (4-59%) and amnion epithelial cells (8-19%) were capable of binding 12±5 and 4±1 infected erythrocytes per positive cell, respectively. Further studies designed to compare the mechanism of binding to the amelanotic melanoma cell line and endothelial cells showed the following results. First, that adhesion of infected erythrocytes to these two cell types was parasite stage-specific in that only erythrocytes containing late ring forms, trophozoites, and schizonts bound. Erythrocytes containing early ring forms, which do not attach to venular endothelium in vivo, did not bind to either cell type. Second, erythrocytes infected with trophozoites and schizonts of P. vivax or a knobless strain of P. falciparum, both of which continue to circulate in vivo, did not bind to either target cell type. Third, transmission electron microscopy showed that infected erythrocytes attached to the amelanotic melanoma cells via knobs. We conclude that cultured human endothelial cells and an amelanotic melanoma cell line share common determinants on their surface and that the mechanism of binding to these two different cell types is similar. The amelanotic melanoma cell line offers a useful substitute for endothelial cells in binding studies requiring large numbers of target cells.